Perception of nursing staff towards the application of Professional Nursing Care Model and job satisfaction at Sanjiwani Hospital, Gianyar - Gusti Ayu Krisma Yuntari; Pande Putu Januraga; I Ketut Suarjana (Public Health and Preventive Medicine Archive, 2018)
Background and purpose: Several hospitals in Indonesia have developed a model of nursing care known as MAKP (Professional Nursing Care Model) to improve the quality of nursing services. Sanjiwani Hospital, Gianyar has applied this model. The aim of this study is to explore the perception of nurses towards this approach and assess its association with job satisfaction. Methods: A cross-sectional survey was conducted with 92 nurses working at the inpatient ward at Sanjiwani Hospital, Gianyar. Data were collected from July-August 2017 by interview using questionnaires. Data collected included the characteristics of respondents (age, gender, education, and employment status), nurses’ perception towards the application of MAKP, and nurses’ job satisfaction. Results: Nursing staff demonstrated perception score of ≥15 on leadership elements (68.5%), communication (72.2%), coordination (84.8%), delegation (80.4%), and supervision (66, 3%). Nursing staff with a score of ≥15 in coordination perception (AOR=4.48; 95%CI: 1.14-17.54), delegation (AOR=4.00; 95%CI: 1.21-13.23) and supervision (AOR=3.35; 95%CI: 1.25-8.88) expressed higher job satisfaction. While aspects of leadership (AOR=0.98; 95%CI: 0.29-3.79) and communication (AOR=0.76; 95%CI: 0.19-3.05) were not significantly associated with job satisfaction. Conclusions: The majority of nurses have a positive perception towards the MAKP approach. The better perception on coordination, supervision and delegation are found to increase job satisfaction. The results imply that coordination, supervision and delegation should be considered in order to increase job satisfaction in other hospitals.